Nuclear renaissance: technologies and policies for the future of nuclear power - Nuttall, William J. (Institute of Physics Pub., 2011)
With growing concerns over environmental issues and global energy consumption, there is increasing interest in nuclear power generation, despite its diminished role in the West over the last few decades. Many of those involved with nuclear power and environmental agencies see controlled expansion of nuclear plants as the most environmentally friendly way of meeting growing energy demands.